Classification of reinforced concrete single story and double story house using eco-efficiency index approach - Hamid, M.S.A. (Institute of Physics Publishing, 2019)
In the current construction industry, the selection of structural design was important in order to ensure the design were satisfied in term of economic, environment and social as for the purpose to fulfill need of sustainable development. Eco-efficiency has been introduced to be used for the decision-making method in selection of the best design that fulfill requirement of sustainability. This study was develop to integrate analysis of eco-efficiency index for reinforced concrete structural elements by considering economical score and environmental score as a main approach. The classification of the design case for single story and double story house took place from low level to high level of eco-efficiency based on its eco-efficiency index. Result shows single story house was classified from medium low to medium high eco-efficiency design level for all 10 cases while for double story house was classified from low to high eco-efficiency design level. Â© Published under licence by IOP Publishing Ltd.